Trichoderma Compost for Disease Control and Increasing Rice Production in Subak Taman, Taman Village, Abiansemal, Badung - Andriani, A. A. S. P. R.; Rukmini, Ni Ketut Sri; Mardewi, Ni Ketut; Triyana, Desak Nyoman; Bulu, Irma Yustika; Dahung, Yulianti (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This community service program was carried out as a form of university contribution in helping farmers in Subak Taman, Taman Village, Abiansemal District, Badung Regency, Bali, in increasing rice productivity while tackling plant disease problems, especially those caused by soil pathogens. This activity focused on training and mentoring in making compost enriched with Trichoderma sp., a biological agent proven effective in controlling plant diseases such as root rot and blast disease in rice. In addition to being a biological agent, Trichoderma is also able to accelerate the decomposition of organic matter, increase soil fertility, and support natural plant growth. This activity began with socialization regarding the benefits and role of Trichoderma in an environmentally friendly agricultural system. Next, technical training on making compost based on agrarian waste enriched with Trichoderma. After that, direct practice of making compost with Subak Taman farmers was carried out. The results of the activity showed enthusiasm and active participation from Subak members. Farmers expressed interest in continuing to use Trichoderma compost because they saw its potential benefits for plant health and production results. The target achieved from the activity is that the partner's knowledge of liquid organic fertilizer production technology has increased from 40% to 80%. The use of trichocompost fertilizer in organic rice farming systems can increase dry grain yields by 4.4% to 17.4%. Trichocompost promotes sustainable agriculture by reducing the need for pesticides and synthetic fertilizers, resulting in reduced environmental contamination and preservation of the soil ecosystem.